Development of Prefrontal Cortex Skills in Self-regulation in Early Childhood Children Using Science Experiment Activities to Enhance Learning: Development of Prefrontal Cortex Skills in Self-regulation in Early Childhood Children Using Science Experiment Activities to Enhance Learning - comsai, phenpron; Phorntaweekul, Satjatham (RATANABUTH JOURNAL, 2026)
This research aims to 1) to develop and evaluate the efficiency of science experiment activities designed to enhance learning for early childhood students at Ban Song Witthayakhom School, based on the 80/80 efficiency criterion; and 2) to compare the Executive Function in self-regulation of early childhood students before and after participating in these activities. The study employed a pre-experimental research design. The target group consisted of 14 kindergarten level 3 students during the second semester of the 2025 academic year at Ban Song Witthayakhom School, under the Roi Et Primary Educational Service Area Office 1, selected through The statistics used for data analysis included mean, and percentage standard deviation. The research found that 1) The science experiment activities for early childhood students at Ban Song Witthayakhom School demonstrated an efficiency of 86.11/85.92, which met the predefined 80/80 standard criterion. 2, After participating in the activities, the students’ Executive Function in self-regulation was significantly higher than the pre-determined criteria at the .05 level.